2012
DOI: 10.5194/cp-8-907-2012
|View full text |Cite
|
Sign up to set email alerts
|

The initiation of modern soft and hard Snowball Earth climates in CCSM4

Abstract: Abstract. Geochemical and geological evidence has suggested that several global-scale glaciation events occurred during the Neoproterozoic Era in the interval from 750-580 million years ago. The initiation of these glaciations is thought to have been a consequence of the combined influence of a low level of atmospheric carbon dioxide concentration and an approximately 6 % weakening of solar luminosity. The latest version of the Community Climate System Model (CCSM4) is employed herein to explore the detailed c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 48 publications
6
30
0
Order By: Relevance
“…The remaining difference may be due to the significant difference in sea-ice dynamics between the two models (Voigt and Abbot, 2012), but the present study suggests that this could also be due in part to the different parameterization of aerosols. These new results are similar to those obtained previously using CCSM4 but with the present-day continents (70-100 ppmv) (Yang et al, 2012c). The high-latitude continental configuration (570 Ma) is found to be more conducive to global glaciation than the low-latitude continent distribution (720 Ma) in the CCSM3 model.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The remaining difference may be due to the significant difference in sea-ice dynamics between the two models (Voigt and Abbot, 2012), but the present study suggests that this could also be due in part to the different parameterization of aerosols. These new results are similar to those obtained previously using CCSM4 but with the present-day continents (70-100 ppmv) (Yang et al, 2012c). The high-latitude continental configuration (570 Ma) is found to be more conducive to global glaciation than the low-latitude continent distribution (720 Ma) in the CCSM3 model.…”
Section: Discussionsupporting
confidence: 89%
“…As important, however, concerning their results is the fact that this model delivered stable slushball solutions in which the sea-ice front lay considerably equatorward of 25-30 • latitude. When a more advanced version of the model, CCSM4, was employed, these critical values at the bifurcation point were found to increase moderately to 0.91-0.92TSI 0 and 70-100 ppmv, respectively (Yang et al, 2012c). Therefore, the conditions required for the initiation of a hard snowball Earth have been found to be highly model dependent, the transition being much easier to achieve in the ECHAM5/MPI-OM than in either the CCSM3 or CCSM4 models.…”
Section: Y Liu Et Al: the Initiation Of Neoproterozoic "Snowball" Cmentioning
confidence: 99%
“…With Marinoan continents, the ECHAM5/Max Planck Institute Ocean Model (MPI-OM) model predicts a snowball state when solar luminosity is reduced below 96% of the modern value with preindustrial greenhouse gas concentrations . A follow-up study using CCSM, version 4 (CCSM4), showed similar, but slightly less extreme, initiation thresholds (Yang et al 2012a). Yang et al (2012b,c) find snowball states in the fully coupled Community Climate System Model, version 3 (CCSM3), model when TSI is reduced by 10%-10.5% with preindustrial greenhouse gas concentrations or by 6% with a strong greenhouse gas reduction to 17.5 ppmv CO 2 .…”
Section: Introductionmentioning
confidence: 91%
“…Yang et al (2012c) point out that the spatial pattern of forcing by changes in CO 2 is uniform, while TSI changes have a stronger absolute forcing in the tropics than at the poles (their Fig. Yang et al (2012c) point out that the spatial pattern of forcing by changes in CO 2 is uniform, while TSI changes have a stronger absolute forcing in the tropics than at the poles (their Fig.…”
Section: A Climate Sensitivity To Tsi Changesmentioning
confidence: 99%
“…Lewis et al, 2007;Peltier et al, 2007;Peltier, 2010, 2011;Pierrehumbert et al, 2011). Several recent studies with fully coupled atmosphere-ocean models have suggested that the CO 2 threshold is quite strongly model dependent, ranging from 17.5-20 ppmv in CCSM3 (Yang et al, 2012a,b), 86 ppmv in MIROC-lite (Oka et al, 2010), 70-100 ppmv in CCSM4 (Yang et al, 2012c), to 278 ppmv in ECHAM5/MPI-OM (Voigt and Marotzke, 2010;Voigt et al, 2011), when there is a 6 % reduction in solar luminosity. For deglaciation is assumed, simulations with different models have also suggested different thresholds (Hyde et al, 2000;Tajika, 2003;Pierrehumbert, 2004Pierrehumbert, , 2005Le Hir et al, 2007).…”
Section: Introductionmentioning
confidence: 99%